Pengaruh Pembiayaan Mudharabah, Musyarakah, dan Ijarah Terhadap Net Profit Bank Syariah Indonesia (Periode 2021-2023) The Effect of Mudharabah, Musyarakah, and Ijarah Financing on Net Profit of Bank Syariah Indonesia (2021-2023 Period) - Riska Dwi Sari; Tuti Anggraini; Ahmad Syakir (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2024)
This study examines the impact of Mudharabah, Musyarakah, and Ijarah financing on Bank Syariah Indonesia's net profit from 2021-2023. Using a quantitative approach and secondary data from the bank's monthly reports (2020-2023), multiple linear regression analysis was performed with Eviews 12 software. Results indicate that Mudharabah financing does not affect net profit, while Musyarakah financing does, and Ijarah financing does not. Collectively, these financings significantly influence the net profit, accounting for 50.4% of the variation, with the remaining 49.6% due to other factors.